Penerapan Food Cost Control Process Kaitannya dengan Penjualan Makanan dalam Meningkatkan Laba pada F & B Departemen (Studi Kasus pada Hotel Salak Bogor) - Adri Wihananto (STIE Binaniaga, 2010)
The cost of food production was costs that were spent to process the food material into a food product, that consisted of the food cost, labor cost and overhead cost The cost of food production was the important matter that must be paid attention to in the determination of the selling price and as the foundation of management decision making in the achievement of the purpose that is the profit. Because of that the management must carry out the control towards the level of the cost of the food raw material so that the profit that was reached could be more increased. The purpose of this research was to know the application of the process of the control of his cost of the raw material of connection food with the sale in increasing the dirty profit in food and beverage department the Salak Hotel Bogor, Controlling was done purpose at controlling the cost of the food raw material, controlled the quality of the food product that was produced, as well as reached the profit target that was determined. The research that was carried out by the writer was in food and beverage department the Salak Hotel Bogor that was located in Bogor. Food and Beverage Department was to be one of the sources of the income for the Salak Hotel Bogor through the food and beverage sales. Results of the research showed that generally food and beverage department the of Salak Hotel Bogor carried out the control against the cost of the food raw material by being good enough, through the process of the mechanism of the control that was carried out continuously that involved several functions, from the function of the purchase, receive the storage and the issuing, the production to finally the food product finally arrive in the guest table was as the product sold. This matter was proven with the achievement of the standard of the percentage of the cost of the food raw material that was maintained by the management, so as the profit target that was appointed to be able to be fulfilled. Results of the application to the control of the cost of food production in this research showed that there is several matters that were not yet carried out well by food and beverage department the Salak Hotel Bogor, that is not yet applied by him the standard recipe, standard portion size, and the standard portion cost that will cause the use of the food material in a excessive and giving of the price that did not follow the change in the price of the food material. If the application of the control to the three matters went again better ate the price level of the subject of food that emerged was able to be able to be minimised to maximise the profit that was received. That was caused by the existence of relations that were close between food cost price, the sale and the profit that was produced.